Early gastrogastric fistula after Roux-en-Y gastric bypass: successful fistula treatment with self-expandable endoscopic stent - Süsstrunk, Julian (BMJ Case Rep, 2021)
A 25-year-old patient underwent laparoscopic Roux-en-Y gastric bypass surgery with an initially uneventful postoperative course. Two weeks postoperatively, the patient presented with acute abdominal pain. CT scan revealed a gastrogastric fistula from the gastric pouch to the gastric remnant. Laparoscopic drainage was performed, and intraoperative endoscopy confirmed a large gastrogastric fistula. Due to intense adhesions between pouch and remnant, a closure by suture of the fistula was not possible. The fistula was initially treated with a fully covered metal stent. After multiple stent migrations despite clip attachment to the mucosa, the stent was changed to a partially covered metal stent. Fistula healing progress was documented every 2 weeks. After 10 weeks of stent treatment, fistula closure was accomplished. In conclusion, early fistula from the gastric pouch to the gastric remnant is a rare complication and can be managed with endoscopic stent placement.